Optimalisasi Pemanfaatan Perpustakaan Desa dalam Peningkatan Literasi Anak Desa Bendoagung - Muhamad Wafiq Chafidudin; Hendra Pratama; Tatik Susanti; Diana Sintawati; Isna Nur 'Azizah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Optimizing the utilization of village libraries is an important strategy in improving children’s literacy in Bendoagung Village. This study examines how the village library can serve as an effective learning resource center to foster reading interest and literacy skills among local children. The approach involves active participation of the community and village officials in managing the library, as well as implementing literacy programs that specifically target children as the main focus. The findings indicate that with improved library management and strong community involvement, village libraries can significantly enhance awareness and reading habits among children in Bendoagung. Furthermore, supporting activities such as reading corners, reading competitions, and the availability of diverse reading materials play a crucial role in cultivating literacy culture from an early age. The library also functions as an inclusive public space where children can learn, interact, and develop confidence through literacy activities. In conclusion, optimal use of village libraries contributes greatly to improving basic education quality by strengthening literacy culture. Therefore, it is recommended that every village consider improving library facilities, providing training for librarians, and encouraging active community roles to sustain literacy programs and shape a smarter, more literate young generation.